A novel error compensation method for an absolute optical encoder based on empirical mode decomposition. (1st May 2017) - Cai, Nian; Xie, Wei; Peng, Hongxia; Wang, Han; Yang, Zhijing; Chen, Xin
Abstract: Absolute optical encoders have emerged as a preferable choice of accurate positioning measurement for high-end manufacturing. To further improve the measurement accuracy of the absolute optical encoder, a novel error compensation method is proposed based on the empirical mode decomposition (EMD) method. This method is operated as follows: First, the measurement error achieved by an absolute optical encoder is decomposed into a number of intrinsic mode functions (IMFs) and the residue based on EMD. Then, a novel Hilbert marginal spectrum (HMS) based scheme is proposed to extract the underlying trend of the measurement error. Finally, the underlying trend is eliminated from the measurement error to improve the measurement accuracy. Experimental results indicate that the proposed compensation method extracts the underlying trend of the measurement error very well and improves the measurement accuracy of the absolute optical encoder. Highlights: An error compensation method is proposed to improve measurement accuracy of an absolute optical encoder. The proposed method is based on empirical mode decomposition. A novel trend extracting scheme is proposed based on the Hilbert marginal spectrum. The proposed method is superior to the traditional EMD-based method.